2017
DOI: 10.18869/acadpub.jafm.73.238.26519
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Optimization of Injection Angle Effects on Fluidic Thrust Vectoring

Abstract: A computational investigation was conducted to optimize the fluidic injection angle effects on thrust vectoring. Numerical simulation of fluidic injection for shock vector control, with a convergent-divergent nozzle concept was performed, using URANS approach with Spalart-Allmaras turbulence model. The fluidic injection angles from 60º to 120º were investigated at different aerodynamic and geometric conditions. The current investigation demonstrated that secondary injection angle is an essential parameter in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…A nozzle with shock-vectoring (Wing 1994) has achieved a vectoring angle of 17.3 degrees at the nozzle pressure ratio (NPR) of 4, however thrust ratio lies between 0.84 and 0.9 and vectoring efficiency takes values between 1.8 to 3.0 degrees per percent secondary injection. In another study pertaining shock-vectoring, Forghany et al (2017) numerically investigated the impact of secondary injection angle varied from 60 to 120 degrees in a convergent-divergent nozzle at different aerodynamic and geometric conditions. Their findings revealed that injection angle provides substantial effects on shock-vectoring performance.…”
Section: Introductionmentioning
confidence: 99%
“…A nozzle with shock-vectoring (Wing 1994) has achieved a vectoring angle of 17.3 degrees at the nozzle pressure ratio (NPR) of 4, however thrust ratio lies between 0.84 and 0.9 and vectoring efficiency takes values between 1.8 to 3.0 degrees per percent secondary injection. In another study pertaining shock-vectoring, Forghany et al (2017) numerically investigated the impact of secondary injection angle varied from 60 to 120 degrees in a convergent-divergent nozzle at different aerodynamic and geometric conditions. Their findings revealed that injection angle provides substantial effects on shock-vectoring performance.…”
Section: Introductionmentioning
confidence: 99%
“…Erdem and Kontis [30] carried out numerical simulations and experiments to analyze the transverse injection, then Erdem et al [31] investigated experimentally the penetration characteristics of the transverse sonic jets in Mach 5 cross flows for air, carbon dioxide, and helium. Forghany et al [32] studied numerically the effect of the fluidic injection angle on TVC system efficiency. Chandra Sekar et al [33] carried out an experimental work to achieve FTV in the yaw direction by transverse injection in a converging nozzle with an elliptic exit and triangular after.…”
Section: Introductionmentioning
confidence: 99%
“…MTV is also used to augment the conventional control surfaces effectiveness, whereas novel flow control concept termed as fluidic thrust vectoring (FTV) which relies on using a secondary jet to deflect the primary jet has attracted much attention in recent times. FTV concept has gained considerable interest due to the presence of few or no moving parts [6,7] as well as faster dynamic response as compared to MTV [8].…”
Section: Introductionmentioning
confidence: 99%
“…Co-flow is found to be amenable for sub-sonic jets, whereas other mentioned techniques are better suited for supersonic jet regimes. In recent times, the focus of FTV in particular has been for supersonic flows as typically encountered in next generation launch vehicles [10][11][12] and aircrafts [9,13,14 and references therein). Nonetheless, co-flow thrust vectoring actuation subject of this work is relevant to sub-sonic unmanned aerial vehicles (UAVs) application [15].…”
Section: Introductionmentioning
confidence: 99%